The aspirin resistance and platelet's receptors expression in chronic heart failure patients with type 2 diabetes mellitus - Kolesnyk, M. Yu.; Syvolap, V. V.; Колесник, Михайло Юрійович; Сиволап, Віталій Вікторович; Сыволап, В. В. (Zaporozhye state medical university, 2014)
Aim. Chronic heart failure and type 2 diabetes mellitus are closely inter-related conditions through different pathological mechanisms, including platelet activation. The aim of our study was to estimate the prevalence of aspirin resistance in heart failure patients with type 2 diabetes mellitus and to clarify platelets` abnormalities according to glycemic control status. Methods and results. We studied 65 patients with heart failure and type 2 diabetes mellitus. Platelet function was evaluated using standard light transmission aggregometry. Measurements of CD41, CD41a, CD61 and CD62P were carried out by fl uorescent microscopy study. The plasma levels of soluble P-selectin and soluble CD40L were measured by ELISA assays. Among the studied patients, 23.1 % were aspirin-resistant by ADP-induced platelet aggregation test and 36.1 % after the use of epinephrine-induced platelet aggregation test. The poor glycemic control in patients with chronic heart failure was associated with high plasma P-selectin level and high CD41 and CD61 expression. Conclusion. The study fi ndings confi rm the role of glycemic control status in prevention of thrombotic complications in chronic heart failure patients with type 2 diabetes mellitus. Хронічна серцева недостатність і цукровий діабет 2 типу тісно пов’язані спільними патогенетичними механізмами, включаючи активацію тромбоцитів. З метою вивчення залежності тромбоцитарної дисфункції від контролю глікемії у 65 хворих дослідили стан агрегації тромбоцитів, рівень експресії рецепторів CD41, CD41a, CD61 і CD62P методом імунофлуоресценції. Рівень розчинних P-cелектину та ліганду СD40L визначили у плазмі імуноферментним методом. Встановили, що за даними АДФ-індукованої агрегації тромбоцитів поширеність аспіринорезистентності становить 23,1%, а за результатами адреналін-індукованої агрегації тромбоцитів – 36,1%. У пацієнтів із незадовільним контролем глікемії спостерігали вірогідне збільшення рівня розчинного Р-селектину та експресії рецепторів СD41 та СD61. Це свідчить про важливість контролю глікемії у профілактиці тромботичних ускладнень у хворих на хронічну серцеву недостатність із супутнім цукровим діабетом 2 типу. Хроническая сердечная недостаточность и сахарный диабет 2 типа тесно связаны между собой общими патогенетическими механизмами, включая активацию тромбоцитов. С целью изучения зависимости тромбоцитарной дисфункции от контроля гликемии у 65 пациентов исследовали процесс агрегации тромбоцитов, уровень экспрессии рецепторов CD41, CD41a, CD61 и CD62P методом иммунофлуоресценции. Уровень растворимых P-cелектина и лиганда СD40L определяли в плазме иммуноферментным методом. Установлено, что по данным АДФ-индуцированной агрегации тромбоцитов распространенность аспиринорезистентности составляет 23,1%, а по результатам адреналин-индуцированной агрегации тромбоцитов – 36,1%. У пациентов с неудовлетворительным контролем гликемии наблюдали достоверное увеличение уровня растворимого Р-селектина и экспрессии рецепторов СD41 и СD61. Это свидетельствует о важности контроля гликемии в профилактике тромботических осложнений у пациентов с хронической сердечной недостаточностью и сопутствующим сахарным диабетом 2 типа.
Аспіринорезистентність та експресія рецепторів тромбоцитів у хворих на хронічну серцеву недостатність
Аспиринорезистентность и экспрессия рецепторов тромбоцитов у пациентов с хронической сердечной недостаточностью и сахарным диабетом 2 типа
Keywords: Aspirin; Drug Resistance; Chronic Disease; Heart Failure; Platelet Activation; Type 2 Diabetes Mellitus; аспіринорезистентність; хронічна серцева недостатність; активація тромбоцитів; цукровий діабет 2 типу; аспиринорезистентность; хроническая сердечная недостаточность; активация тромбоцитов; сахарный диабет 2 типа